Recent Advances in Bacterial Amelioration of Plant Drought and Salt Stress - Elisa Gamalero; Bernard R. Glick (Biology, 2022)
The recent literature indicates that plant growth-promoting bacteria (PGPB) employ a range of mechanisms to augment a plant’s ability to ameliorate salt and drought stress. These mechanisms include synthesis of auxins, especially indoleacetic acid, which directly promotes plant growth; synthesis of antioxidant enzymes such as catalase, superoxide dismutase and peroxidase, which prevents the deleterious effects of reactive oxygen species; synthesis of small molecule osmolytes, e.g., trehalose and proline, which structures the water content within plant and bacterial cells and reduces plant turgor pressure; nitrogen fixation, which directly improves plant growth; synthesis of exopolysaccharides, which protects plant cells from water loss and stabilizes soil aggregates; synthesis of antibiotics, which protects stress-debilitated plants from soil pathogens; and synthesis of the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase, which lowers the level of ACC and ethylene in plants, thereby decreasing stress-induced plant senescence. Many of the reports of overcoming these plant stresses indicate that the most successful PGPB possess several of these mechanisms; however, the involvement of any particular mechanism in plant protection is nearly always inferred and not proven.